Student engagement and academic performance of students of Partido State University - Delfino, Armando P. (Universiti Teknologi MARA, 2019)
This research determined the extent of student engagement at Partido State University and analyzed the factors affecting student engagement. Moreover, it investigated the correlation between student engagement and academic performance. The study used descriptive-correlational method. A teacher made questionnaire was used to gather data. The general weighted average for two semesters were used to determine the academic performance of the respondents. Focused group discussion was used to validate the data obtained from the questionnaires. A total of three hundred and five students from the College of Education took part in the study. Mean and ranking, Pearson moment correlation, and multiple regression were used to treat the data. The study revealed that the level of student engagement along behavioral, emotional and cognitive engagements were high with a mean of 2.84. It was found out that academic performance of the respondents was very good (GWA=1.83). The correlational analysis found that teacher (r=.125, p=.029), school (r=.143, p=.013), and family factors (r=.106, p=.028) were possitively related to student engagement, while the Multiple Linear Regression analysis revealed that there was relatively low percentage of variance (1.8%) but shows that the factors were significant predictors of student engagement F(3, 301)=2.905. Furthermore, it was found out that behavioral, emotional and cognitive engagements were positively correlated to the academic performance of the students. The teacher, the school, and the parents should have strong collaboration to provide more opportunities for students to maximize their university engagement.